Labor - Chamberlain, Neil W. (New York, 1958)
This book originated as a series of lectures designed for an introductory course in labor. It falls into two parts. The first thirteen chapters examine the organizations of labor and business and the collective-bargaining relationship between them. The rest of the book explores the impact of unionism on the economy. The objective is not only to acquaint the student with specific issues and problems but to permit an over-all assessment of the economic significance of unions in the United States.
Keywords: Economics